The role of the Polish Agency for Audit Oversight and common courts in disciplinary proceedings against statutory auditors: de lege lata and de lege ferenda remarks (Ius Novum, 2024)
This article is of a scientific and research nature, covering the role of the Polish Agency for Audit Oversight (Polska Agencja Nadzoru Audytowego – PANA) and common courts in disciplinary proceedings against statutory auditors. The research aims to determine whether the provisions of Directive 2006/43/EC and Regulation (EU) 537/2014 justify assigning the aforementioned Agency the status of an authority for proceedings concerning disciplinary offences committed while performing assurance or related services in compliance with national professional standards. The provisions of European Union law regarding the role of public supervision bodies of auditors and audit firms are analysed, and the results are compared with the constitutional and systemic conditions for shaping the norms of disciplinary proceedings. Some de lege ferenda proposals regarding the regulation of disciplinary proceedings bodies in matters concerning statutory auditors are put forward.
Keywords: disciplinary proceedings, auditors, Polish Agency for Audit Oversight